Organizational effectiveness and its role in achieving administrative excellence in student activities departments at some Iraqi universities from the perspective of those working therein - Kadhim, Asst. Prof. Dr. Saif Mohammed; Turki, L. Dr. Duaa Zuhair; Hamidi, Asst. L. Zaid Abdul Zahra (Sulaimani Journal for Humanities, 2026)
The importance of the study emerged in highlighting one of the principles of achieving sustainable development, which is achieving excellence in performance. Therefore, the researchers resorted to choosing one of the principles of modern management, namely organizational effectiveness, as it contributes to achieving efficiency, adapting to external conditions, and achieving sustainability in work. The study explored whether it is possible to benefit from it in achieving excellence in administrative work. Therefore, it was applied to university institutions through the student activities department of some Iraqi universities. Thus, the study aimed to identify the role of organizational effectiveness in achieving administrative excellence in some Iraqi universities from the point of view of their employees. The study was applied to a sample of 264 individuals representing the employees in the student activities departments in some Iraqi universities, representing (38.70%) of the research population. After exclusion and division of the exploratory research samples, preparation and application, the researchers adopted all the necessary scientific steps in preparing the two study scales. The Organizational Effectiveness Scale with its (51) items and the Administrative Excellence Scale with its (31) items were finalized and were able to measure what they were designed to measure. After applying the two study scales, the researchers reached several conclusions, the most important of which is that the student activities departments in some Iraqi universities enjoy organizational effectiveness in their functional performance. The senior leadership of the student activities departments in some Iraqi universities seeks to achieve administrative excellence. Organizational effectiveness has a positive role in achieving and enhancing the administrative excellence of the student activities departments in some Iraqi universities.